2021
DOI: 10.3934/amc.2020067
|View full text |Cite
|
Sign up to set email alerts
|

An explicit representation and enumeration for negacyclic codes of length 2^kn over \mathbb{Z}_4+u\mathbb{Z}_4

Abstract: In this paper, we give an explicit representation and enumeration for negacyclic codes of length 2 k n over the local non-principal ideal ring R = Z 4 + uZ 4 (u 2 = 0), where k, n are arbitrary positive integers and n is odd. In particular, we present all distinct negacyclic codes of length 2 k over R precisely. Moreover, we provide an exact mass formula for the number of negacyclic codes of length 2 k n over R and correct several mistakes in some literatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…A prime example of a gamma-ray emission interpreted as the result of accelerated electrons is the Crab Nebula, the brightest source of the TeV sky, and thus one of the best studied objects [26][27][28]. More generally, several theoretical works have illustrated that electrons accelerated above 100 TeV could lead, through inverse Compton scattering or bremsstrahlung, to gamma rays in the 100 TeV range (see e.g., [9] and references therein), and can produce hard gamma-ray spectra extending up to the 100 TeV, making it especially strenuous to differentiate between hadronic and leptonic acceleration mechanisms [29].…”
Section: Tev Gamma Raysmentioning
confidence: 99%
See 4 more Smart Citations
“…A prime example of a gamma-ray emission interpreted as the result of accelerated electrons is the Crab Nebula, the brightest source of the TeV sky, and thus one of the best studied objects [26][27][28]. More generally, several theoretical works have illustrated that electrons accelerated above 100 TeV could lead, through inverse Compton scattering or bremsstrahlung, to gamma rays in the 100 TeV range (see e.g., [9] and references therein), and can produce hard gamma-ray spectra extending up to the 100 TeV, making it especially strenuous to differentiate between hadronic and leptonic acceleration mechanisms [29].…”
Section: Tev Gamma Raysmentioning
confidence: 99%
“…was capable of claiming the detection of the first pevatron in the Galactic center region [39]. Other observatories, using different techniques, relying on shower front detectors (or "air shower detectors"), such as HAWC [40], Tibet ASγ [41] and LHAASO [28], operating up to and above the ∼100 TeV gamma-ray domain also reported on the detection of several Galactic pevatrons. All these observations indicated that most of the pevatron candidates seem to not be associated to SNRs.…”
Section: Tev Gamma Raysmentioning
confidence: 99%
See 3 more Smart Citations